The Therapeutic Effect and Mechanism of Qishen Yiqi Dripping Pills on Cardiovascular and Cerebrovascular Diseases and Diabetic Complications - Zhao, Chunlai; Wang, Wenjia; Yan, Kaijing; Sun, He; Han, Jihong; Hu, Yunhui (Current Molecular Pharmacology, 2022)
The alterations in vascular homeostasis are deeply involved in the development of numerous diseases, such as coronary heart disease, stroke, and diabetic complications. Changes in blood flow and endothelial permeability caused by vascular dysfunction are the common mechanisms for these three types of diseases. The disorders of glucose and lipid metabolism can bring changes in the energy production patterns in endothelium and surrounding cells which may consequently cause energy metabolic disorders, oxidative stress, and inflammatory responses. Traditional Chinese medicine (TCM) follows the principle of the “treatment by the syndrome differentiation.” TCM considers coronary heart disease, stroke, and diabetes complications all as the type of Qi-deficiency and blood stasis syndrome, which mainly occurs in the vascular system. Therefore, the common pathogenesis of these three types of diseases suggests that the treatment strategy by TCM should be in a close manner and referred to as “treating different diseases by the same treatment.” Qishen Yiqi dripping pill is a modern Chinese herbal medicine that has been widely used for the treatment of patients with coronary heart disease characterized as Qi-deficiency and blood stasis in China. Recently, many clinical reports have demonstrated the potential therapeutic effects of Qishen Yiqi dripping pills on ischemic stroke and diabetic nephropathy. Based on these reports, we will summarize the clinical applications of Qishen Yiqi dripping pills on coronary heart disease, ischemic stroke, and diabetic nephropathy, including the involved mechanisms discussed in various research works.
Keywords: stroke